Biopesticides for Managing Pests and Diseases of AICCRA Priority Value Chains - Yeboah, Stephen; Adomako, Joseph; Amankwaa-Yeboah, Patricia; Frimpong-Anin, Kofi; Dalaa, Mustapha A.; Damba, Osman T.; Kyere, Reginal; Obeng, Faustina; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The approach was used to disseminate site-specific climate-information services, agro advisories, and climate-smart agriculture technologies for AICCRA Ghana Cluster priority value chains